Did Modern Human Dispersal Take a Coastal Route into India? New Evidence from Palaeolithic Surveys of Kachchh, Gujarat. (4th May 2017) - Blinkhorn, James; Ajithprasad, P.; Mukherjee, Avinandan
ABSTRACT: The Indian Ocean coastline is argued to have been a critical route of modern human dispersal from Africa, introducing Late Palaeolithic industries into South Asia, but a dearth of evidence has prevented a direct evaluation of this. Kachchh (Gujarat, India), located immediately east of the Indus Delta, is an important setting to appraise the Palaeolithic occupation of the western Indian coastline. Targeted survey of Late Pleistocene sediments there found widespread evidence for occupation of Kachchh during the Late Pleistocene: Middle Palaeolithic and possibly Late Acheulean lithic artifacts. The conspicuous absence of Late Palaeolithic industries in these Late Pleistocene deposits, with their presence only noted in Holocene contexts, does not support the model of modern human expansions into India with these industries via the coastal route. We evaluate these results in the context of current debates regarding Late Pleistocene hominin demography, adaptation, and expansions.